2009
DOI: 10.1080/10508400903013462
|View full text |Cite
|
Sign up to set email alerts
|

The Purchasing Practice of Low-Income Students: The Relationship to Mathematical Development

Abstract: Journal of the Learning SciencesPublication details, including instructions for authors and subscription information:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 30 publications
1
26
0
6
Order By: Relevance
“…Previous studies examining non-dominant students' practices in and out of school contexts have challenged a deficit perspective towards non-dominant students and have collectively highlighted non-dominant people's and communities' competence in collective practices that involve mathematical tools (Baker et al, 2003;Brenner, 1998;Civil, 2007;Gonzalez, Andrade, Civil, & Moll, 2001;Nasir & Hand, 2008;Saxe, 2012;Saxe & Esmonde, 2005;Taylor, 2009). These studies foreground mathematical competence and Bfunds of knowledge ( Moll, Amanti, Neff, & Gonzalez, 1992, p.133), which have traditionally been neglected in school contexts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies examining non-dominant students' practices in and out of school contexts have challenged a deficit perspective towards non-dominant students and have collectively highlighted non-dominant people's and communities' competence in collective practices that involve mathematical tools (Baker et al, 2003;Brenner, 1998;Civil, 2007;Gonzalez, Andrade, Civil, & Moll, 2001;Nasir & Hand, 2008;Saxe, 2012;Saxe & Esmonde, 2005;Taylor, 2009). These studies foreground mathematical competence and Bfunds of knowledge ( Moll, Amanti, Neff, & Gonzalez, 1992, p.133), which have traditionally been neglected in school contexts.…”
mentioning
confidence: 99%
“…For example, historical and longitudinal accounts of the Oksapmin people's 27-body-part counting system illuminate how the counting system has been reproduced and altered along with the shift in political, economic, and educational macro systems in Papua New Guinea (Saxe, 2012;Saxe & Esmonde, 2005). Taylor's (2009) analysis of low-income African American children's purchasing practices in the United States demonstrated the direct influences of macro system (such as concentrations of poverty and taxation policies) on the practices in which these children engage. Nasir and Hand (2008) compared students' practices in mathematics classrooms and basketball games, and highlighted practicelinked identity as one of the significant layers of practice that supported students' engagement.…”
mentioning
confidence: 99%
“…Many studies have established that economic practices such as buying and selling are sites for the development of arithmetical knowledge (Guberman, 1996;Khan, 1999;Saxe, 1991;Taylor, 2009). These studies showed that children can learn numeric and arithmetic understandings and operations through exchanges, such as using coins and bills as a support in calculating total price and developing arithmetic strategies for pricing goods (Guberman, 1996;Saxe, 1991;Taylor, 2009).…”
Section: Economic Practicesmentioning
confidence: 99%
“…These studies showed that children can learn numeric and arithmetic understandings and operations through exchanges, such as using coins and bills as a support in calculating total price and developing arithmetic strategies for pricing goods (Guberman, 1996;Saxe, 1991;Taylor, 2009).…”
Section: Economic Practicesmentioning
confidence: 99%
See 1 more Smart Citation